PERANCANGAN CREATIVE CENTER DENGAN PENERAPAN ARSITEKTUR KONTEMPORER DI CIPUTAT, TANGERANG SELATAN - Deni Basuki Kurniawan; Anggraeni Dyah Sulistiowati; Tri Endangsih (MAESTRO, 2021)
The Creative Industry is one of the world's economic sectors that is growing rapidly at this time, and Indonesia is no exception. With the diversity of ethnic groups in Indonesia, making several creative products in Indonesia are very diverse in number and can compete in domestic and international markets. South Tangerang City is a city located in a strategic position close to the capital city of Jakarta. South Tangerang has a number of demographics that are dominated by the younger generation. With a dominating youth population, South Tangerang City needs more facilities to advance its young generation to actively contribute to the Creative Industry sector. One of the facilities needed is a Creative Center that functions as a gathering place for Creative Industry players to collaborate, produce, train and hone the potential that exists in the younger generation in Indonesia so that they can actively contribute to the Creative Economy sector in Indonesia. The concept of Contemporary buildings is considered capable of representing the characteristics of young people who are active, dynamic and like new things. Keywords: Contemporary Architecture, Creative Center, South Tangerang City.